2020
DOI: 10.21037/gs-20-466
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic body posture after unilateral mastectomy: a pilot study

Abstract: Background: Postural changes after unilateral mastectomy may appear in relation to the dominant hand, postoperative duration, and dynamic conditions. This study aimed to compare the postural changes by inclination angles and muscle activities in the static and dynamic sitting position between women with breast cancer who underwent mastectomy and women who did not have breast cancer.Methods: The observational study design was conducted. We evaluated 17 women who underwent modified radical mastectomy (MRM) more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Among the recently discussed breast cancer issues is the postural control assessment in women after mastectomy [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. A review of the above-mentioned publications indicated that the undertaken research was concerned with the impact of mastectomy on body static conditions [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ] and body posture of women who had received mastectomies [ 7 , 10 , 18 , 19 ,…”
Section: Introductionmentioning
confidence: 99%
“…Among the recently discussed breast cancer issues is the postural control assessment in women after mastectomy [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. A review of the above-mentioned publications indicated that the undertaken research was concerned with the impact of mastectomy on body static conditions [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ] and body posture of women who had received mastectomies [ 7 , 10 , 18 , 19 ,…”
Section: Introductionmentioning
confidence: 99%
“…The reduced invasiveness of breast cancer surgical treatment is a widely acknowledged preference; hence, there is a tendency to perform the breast-conserving procedure, which increase the quality of patient’s life ( 7 , 8 ). Nevertheless, sometimes it is necessary surgical treatment to remove the entire tumor along with the entire mammary gland, the fascia of the pectoralis major, and the lymph nodes (Modified Radical Mastectomy or Simple Mastectomy), which is always associated with a structural and functional deficit ( 2 , 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…In studies on the population of women after mastectomy, the most attention is paid to issues related to psychologic parameters, such as lack of acceptance of one’s own body, reduced attractiveness, and sexuality ( 14 16 ). Some studies have also reported numerous functional disorders resulting mainly from an extensive wound, scarring, swelling, limited mobility in the joints of the shoulder girdle, and low muscle strength on the operated side ( 9 , 13 , 17 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations